Financial repression in general equilibrium: The case of the United States, 1948-1974 - Martin Kliem; Alexander Kriwoluzky; Gernot J. Müller; Alexander Scheer (Deutsches Institut für Wirtschaftsforschung (DIW), 2024)
Financial repression lowers the return on government debt and contributes, all else equal, towards its liquidation. However, its full effect on the debt-to-GDP ratio hinges on how repression impacts the economy at large because it alters investment and saving decisions. We develop and estimate a New Keynesian model with financial repression. Based on U.S. data for the period 1948-1974, we find, consistent with earlier work, that repression was pervasive but gradually phased out. A model-based counterfactual shows that GDP would have been 5 percent lower, and the debt-to-GDP ratio 20 percentage points higher, had repression not been phased out.
Keywords: H63; E43; G28; 330; Financial repression; Government debt; Interest rates; Banks; Regulation; Bayesian estimation